Rural Dwellers’ Perception of Human Trafficking and its Implication for Agricultural Production in Edo State, Nigeria - A. U, Ofuoku; U. N, Uzokwe (Asian Journal of Agriculture and Rural Development, 2012)
This study was carried out to ascertain the perception of rural dwellers on human trafficking in relation to its effect on agricultural production in the three Senatorial Districts of Edo State, Nigeria. A sample size of 120 household heads was used for the study. Structured questionnaire and interview schedule were used to collect data for the study. The data were analyzed using frequency counts, means and percentage while Chi-Square statistical model and Tobit regression analytical model were used to test the hypotheses. It was discovered that the household members were trafficked as a result of push and pull factors. The trafficked members of household were actively involved in farming practices before being trafficked. There is significant relationship between human trafficking and agriculture production. Shortage of farm labor, decreased farm size, reduced farm income, reduced farm output, extra expenditure on hired labor and storage of food supply by the community were perceived as effect of human trafficking on agriculture. Age of the household head and the household size had significant effect on the number of household member trafficked. Human trafficking has an adverse effect on agricultural production. Extension department should therefore integrate anti-human trafficking campaigns with their services to the farming population.